2009
DOI: 10.1149/1.3095517
|View full text |Cite
|
Sign up to set email alerts
|

Sintering Effects on Proton Conductivity of Ta-Doped Ba[sub 2](CaNb)[sub 2]O[sub 6] and its Reactivity with SOFC Cathodes

Abstract: The effect of preparation temperature on electrical conductivity of Ba 2 ͑Ca 0.75 Nb 0.59 Ta 0.66 ͒O 6−␦ , Ba 2 ͑Ca 0.75 Nb 0.66 Ta 0.59 ͒O 6−␦ , and Ba 2 ͑Ca 0.79 Nb 0.66 Ta 0.55 ͒O 6−␦ was investigated in air and humidified N 2 and O 2 . Powder X-ray diffraction ͑PXRD͒ showed the formation of double-perovskite-type structure. Among the compounds investigated, Ba 2 ͑Ca 0.79 Nb 0.66 Ta 0.55 ͒O 6−␦ showed the highest proton conductivity of 3.7 and 5.3 ϫ 10 −4 S/cm at 550°C in wet N 2 , respectively, for a 1400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[26][27][28][29][30] Most of the studies on LSM indicate that LSM does not react with the Ba-containing materials. [31][32][33] However, considering the polarization effect, particularly the strong corrosivity of nitrate under polarization and heating, [34][35][36] the reaction between the electrode materials and the Ba compounds is possible. Traulsen et al 12 reported a distinct change in the microstructure on the LSM/CGO cell stacks inltrated with BaO aer the electrochemical test and attributed it to the reaction between BaO and LSM/CGO under the test conditions.…”
Section: Degradation Related To the Microstructure Changementioning
confidence: 99%
“…[26][27][28][29][30] Most of the studies on LSM indicate that LSM does not react with the Ba-containing materials. [31][32][33] However, considering the polarization effect, particularly the strong corrosivity of nitrate under polarization and heating, [34][35][36] the reaction between the electrode materials and the Ba compounds is possible. Traulsen et al 12 reported a distinct change in the microstructure on the LSM/CGO cell stacks inltrated with BaO aer the electrochemical test and attributed it to the reaction between BaO and LSM/CGO under the test conditions.…”
Section: Degradation Related To the Microstructure Changementioning
confidence: 99%
“…6). The existence of proton conduction in perovskite-type structures has been well-established in the literature [31][32][33][34][35][36][37][38][39][40][41][52][53][54][55][56][57][58][59][60][61][62][63][64]; therefore, it will not be elaborated in this work. We have investigated the chemical stability of BCTY in CO 2 .…”
Section: Electrical Characterization Of Bctymentioning
confidence: 99%
“…During the heating and cooling runs, the Arrhenius plots fall on the same line, which verifies the equilibrium conductivity behavior. Several investigators have determined that the increase in electrical conductivity of acceptor-doped perovskites (e.g., ABO 3 A = Sr, Ba; B = Zr, Ce) and related ordered double perovskite-type Ba 3 CaNb 2 O 9 structures in wet atmospheres is primarily a result of proton conduction[52][53][54][55][56][57][58][59][60][61][62][63][64]. Among the samples studied, 5 mol% Ti-doped BaCe 0.75 Ti 0.05 Y 0.2 O 3-δ showed the highest electrical conductivity of 2.52×10 −3 S cm −1 at 650°C in H 2 +3% H 2 O (…”
mentioning
confidence: 99%
“…35 Also, we noticed a similar effect for Ta-doped double perovskite-type Ba 3 CaNb 2 O 9 and In-doped CeO 2 . 27, 30 Hence, only data points in the frequency range from 0.01 Hz to 1 MHz were reported. In general, one would anticipate a minimum of three contributions, for polycrystalline electrolytes, due to bulk, grain-boundary and electrode polarization over the wide range of the investigated frequency.…”
Section: Ac Impedance Of In-doped Ceomentioning
confidence: 99%